2013
DOI: 10.1182/blood-2012-09-399725
|View full text |Cite
|
Sign up to set email alerts
|

Biologic and clinical significance of somatic mutations of SF3B1 in myeloid and lymphoid neoplasms

Abstract: Precursor mRNA splicing is catalyzed by the spliceosome, a macromolecule composed of small nuclear RNAs associated with proteins. The SF3B1 gene encodes subunit 1 of the splicing factor 3b, which is important for anchoring the spliceosome to precursor mRNA. In 2011, wholeexome sequencing studies showed recurrent somatic mutations of SF3B1 and other genes of the RNA splicing machinery in patients with myelodysplastic syndrome or myelodysplastic/myeloproliferative neoplasm. SF3B1 mutations had a particularly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
106
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 65 publications
3
106
1
2
Order By: Relevance
“…15,43,47 It has been suggested that multipotent hematopoietic stem cells initially attain a splicing factor mutation as a founding genetic lesion, and subsequently acquire additional mutations that drive their malignant transformation. 43,48 This is consistent with our finding in one 5q-syndrome case with a high SF3B1 mutant allele frequency and two other mutations (ASXL1 and TET2) with lower mutant allele frequencies.…”
Section: 漏 F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 81%
“…15,43,47 It has been suggested that multipotent hematopoietic stem cells initially attain a splicing factor mutation as a founding genetic lesion, and subsequently acquire additional mutations that drive their malignant transformation. 43,48 This is consistent with our finding in one 5q-syndrome case with a high SF3B1 mutant allele frequency and two other mutations (ASXL1 and TET2) with lower mutant allele frequencies.…”
Section: 漏 F E R R a T A S T O R T I F O U N D A T I O Nsupporting
confidence: 81%
“…Similarly, mutations in PRPF8 have been identified in MDS and AML patients where decreased PRPF8 expression is associated with increased exon skipping [53], possibly due to a splicing proofreading defect [53]. While DDX41 R525H is associated with reduced binding to SF3B1 and PRPF8, DDX41 mutations have not been reported in association with MDS with ring sideroblasts that is often characteristic of mutations in SF3B1 [50] and PRPF8 [53].…”
Section: Ddx41 In Mrna Splicingmentioning
confidence: 99%
“…Somatic mutations in SF3B1 are frequently found in MDS and chronic lymphocytic leukemia (CLL) patients [50,51]. Studies suggest that mutations in SF3B1 induce malignancy through aberrant transcription, altered pre-mRNA recognition and alternative splicing [50,52]. Similarly, mutations in PRPF8 have been identified in MDS and AML patients where decreased PRPF8 expression is associated with increased exon skipping [53], possibly due to a splicing proofreading defect [53].…”
Section: Ddx41 In Mrna Splicingmentioning
confidence: 99%
See 1 more Smart Citation
“…SF3B1 is the core protein of snRNP in classical spliceosome. Its role is to recognize the branch side of premRNA, and, subsequently, to bind it with the spliceosome, what is the initial stadium of splicing [57,58]. The abnormalities of this regulation, which are associated with the mutations in SF3B1 gene, may lead to unintended introns retention, and, consequently, to forming alternative, modified transcripts [59].…”
Section: Sf3b1mentioning
confidence: 99%